System productivity, nutrient uptake and nutrient balance in the wheat-mungbean-t. Aman rice cropping system (Bangladesh Journal of Agricultural Research, 2017)
System productivity, nutrient uptake and apparent nutrient balance in the wheatmungbean- T. aman rice cropping system was studied. The experiment comprised four treatments-absolute nutrient control (T1); farmer’s practice (T2); AEZ basis fertilizer application (T3) and soil test basis fertlizer application (T4). The treatments were compared in a RCBD with three replications over two consecutive years, 2008-09 and 2009-10. The experiment was conducted in Chhiata clay loam soil. The average yields of wheat, mungbean and T. aman ranged from 1415 to 3096 kg ha-1, 1020 to 1463 kg ha-1 and 2999 to 4282 kg ha- 1, respectively showing T4 as the best treatment. The same treatment (T4) demonstrated the highest nutrient uptake by the crops. The apparent balance of N and K (difference between nutrient uptake and nutrient addition) was negative; however it was less negative for T4 treatment. The P balance was positive for all the treatment except T1. Positive S balance was observed in T3 and T4 but negative in absolute control and farmer’s practice. Zinc and B balance was also positive in case of T3 and T4, but negative for T1 and T2 except B. The study suggests soil test basis fertlizer recommendation for the wheatmungbean- T. aman rice cropping system.Bangladesh J. Agril. Res. 42(3): 509-520, September 2017